A Terracotta Mold Discovered in Chartres (France, Eure-et-Loir) with Original Iconography for Apollo - Loïc Androuin; David Wavelet (Les Carnets de l’ACoSt)
In this note, we introduce a mold for a terracotta figurine that represents the god Apollo, whose iconography is unprecedented in the products of central Gaul.